PERLINDUNGAN HUKUM TERHADAP PENDAMPINGAN ANAK SEBAGAI SAKSI KORBAN DALAM PERADILAN ANAK - Wulandari, Made Indri; Lestari, Anak Agung Adi (Jurnal Hukum Mahasiswa, 2024)
Legal protection efforts for children are very important to ensure that their rights are guaranteed and they do not experience additional trauma from the judicial process. Based on the conditions in several scientific work reports and in the case of decision Number 16/Pid. sus-Anak/2021/PN Dps, the author found that there was no mention of the role of assisting children as victim witnesses, which is certainly contrary to legal norms and regulations. The focus of the research problem is legal protection for assisting children as victim witnesses, as well as the process of protecting children as victim witnesses in assistance by related institutions. The research uses empirical legal research. The research results show that the role of related institutions in assisting children as victim witnesses, especially those carried out by UPTD PPA, shows that there is assistance for children as victim witnesses. However, legal protection for assisting children as victim witnesses has not been fully effective because law enforcers still ignore the role of assisting children as victim witnesses so that assistance is rarely provided in the juvenile justice process.